Taṭbīq al-Imlā’ al-Manẓūr bi al-Kharīṭah aż-Żihniyyah Li Tarqiyah Qudrah aṭ-Ṭullāb Fī Tarkīb al-Jumal al-Mufīdah (Dirāsah Tajrībiyah Li al-Marḥalah al-`Āliyah Bi Ma`had Dār al-`Ulūm al-`Aṣrī Banda Aceh) - Isna Isna; Azman Ismail; Buhori Muslim (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2021)
Imla’ is the activity of changing sounds that can be understood into written symbols, but these letters are placed in the correct position of words, to correct the pronunciation and meaning desired. The title of this research is "The Implementation of Imla’ Mandhur through Mind Mapping in Increasing the Students’ Ability in Writing of Complete Sentences (The Experimental Study at Dayah Modern Darul Ulum) ". There are some reasons for the researcher to conduct this research. The low motivation of students. The students were sleepy when the teacher taught in the class. Some of them played with each other and did not pay attention to the lesson. When the teacher instructed them to write the Mufradat, they were unable to write properly and correctly, and some errors were found in writing the Mufradat. As for the difficulty of students in writing Arabic Mufradat, they have not mastered the rules and the way to connect Arabic letters. Besides they also lack vocabulary in writing. The problems that are dealt with by the students, it caused by the monotonous method. The purpose of this study is to increase the student’s ability in Arabic writing by using the Imla’ Mandhur Method through Mind Mapping. It aims to increase the student’s ability in writing. The population was all the students at Modern Darul Ulum, namely 933 students. The sample was 30 students in class X1c as the experimental group and 30 students in X1A as the control group. The researcher used a semi-experimental research design in conducting this research. Post-test and observation were used to collect the data. The result was found that the implementation of Imla’ Mandhur by using Mind Mapping Media can increase the student’s ability in Arabic writing. In this case, the average score for the experimental group was higher than the control group (87, 2 higher than 79.8). It means that the t-test was higher than (t table = 2, 04 from 5% from 1 %).